MOTIVASI BELAJAR DALAM PEMBELAJARAN BAHASA JERMAN SEBAGAI BAHASA ASING DAN HUBUNGANNYA DENGAN TES BAHASA JERMAN - Nira Pradipta Yulianto; Irma Permatawati; Novia Anjani Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study examined students’ learning motivation in German as a foreign language and its relationship with their German achievement. The study employed a descriptive correlational quantitative design. The participants were eleventh-grade students at SMA Kolese De Britto Yogyakarta. The motivation questionnaire initially consisted of 34 items. Following item analysis, 23 items were retained and demonstrated good internal consistency, with a Cronbach’s Alpha coefficient of 0.900. The students’ mean motivation score was 61.94, which was categorized as moderate, while their mean German achievement score was 73.03, categorized as sufficient. As the data did not meet the normality assumption, Spearman’s rank correlation was used. The analysis showed a weak positive relationship between learning motivation and German achievement (ρ = 0.277)). However, the relationship was not statistically significant (ρ = 0.119). These findings indicate that the study did not find sufficient evidence of a significant relationship between the two variables in the group investigated. Other learner and contextual factors may also be associated with students’ German achievement.